[Wetmore, Joan (actor) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Joan Wetmore was born Joan Deery on the 29 August 1911 in Sydney, and was best known for her roles in various films such as Studio One (1948), Young Dr. Malone (1958) and The Nurses (1965), as well as a long career on the stage in the United States. She regularly featured on Broadway from 1938 to 1966 and also worked extensively in the early days of American television. She was married to M. Palmer Dixon.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Wetmore, Joan; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia